Modulating cholesterol-rich lipid rafts to disrupt influenza A virus infection - Li, Yu-Jyun; Chen, Chi-Yuan; Yang, Jeng-How; Chiu, Ya-Fang (Frontiers in Immunology, 2022)
Influenza A virus (IAV) is widely disseminated across different species, and can cause recurrent epidemics and severe pandemics in humans. During infection, IAV attaches to receptors that are predominantly located in cell membrane regions known as lipid rafts, which are highly enriched in cholesterol and sphingolipids. Following IAV entry into the host cell, uncoating, transcription, and replication of the viral genome occurs, after which newly synthesized viral proteins and genomes are delivered to lipid rafts for assembly prior to viral budding from the cell. Moreover, during budding, IAV acquires an envelope with embedded cholesterol from the host cell membrane, and it is known that decreased cholesterol levels on IAV virions reduces infectivity. Statins are commonly used to inhibit cholesterol synthesis for preventing cardiovascular diseases, and several studies have investigated whether such inhibition can block IAV infection and propagation, as well as modulate the host immune response to IAV. Taken together, current research suggests that there may a role for statins in countering IAV infections and modulating the host immune response to prevent or mitigate cytokine storms, and further investigation into this is warranted.